Modifying Soy Hydrolysed Peptide with Tea Saponin and Characterising the Emulsification of the Complex - Xuan XIE; Yuxue YAO; Shizhang YAN; Yao GUAN; Hongfei MA; Shukun SUN; Hao CHEN (Shipin gongye ke-ji, 2023)
In order to analyze the effects of tea saponin (TS) on soy hydrolyzed peptide (SHP) structure and functional properties in SHP-TS complex, comparative analysis SHP and TS were 1:0, 1:0.5, 1:1, 1:2 (w/w) respectively. The Fourier transformed infrared spectrum, fluorescence spectrum and UV-visible absorption spectrum were used to characterize the spatial structural changes of the protein in the SHP-TS complex and to clarify the relationship between SHP conformational changes and functional properties in the complex. The results showed that the addition of TS could change the secondary structure of SHP, and the hydrogen bond was involved in the formation of the SHP-TS complex. SHP strongly interacted with TS and the spatial conformation changes. In addition, the more TS content increased, the more emulsifying and antioxidant properties of the complex were enhanced, the mean of particle size first decreased and then increased, and the absolute value of the ζ-potential first increased and then decreased. When the SHP:TS ratio was 1:1 (w/w), an excellent comprehensive SHP-TS complex was obtained. Compared with the single SHP system, the emulsion stability coefficient of the complex was the highest at this time. The mean particle size of the emulsion was the smallest and the absolute value of the ζ-potential was the highest. This study would provide a theoretical basis for the development of new emulsifiers in the food industry.